Atık pet'in yeniden değerlendirilmesi - Mecit, Oğuz (Fen Bilimleri Enstitüsü, 1992)
Son yıllarda polimerik malzemelerin kullanım alanlarının hızla artmasıyla birlikte özellikle plastik malzemeler başta olmak üzere kullanımı sonrası atılarak hem çevre kirliliği nemde bir değer olan bu malzemelerin yeniden kullanılamama sorunu gündeme gelmiştir. Yapılan bu çalışmada, atık plastik malzemelerden biri olan PET kimyasal yöntemlerle farklı hidroksil bileşikleri varlığında depolimerleştirilerek geri kazanıl mıştır. Depolimerleştirme sistemine etkiyen parametreler saptanmış ve bu parametrelerin son ürün üzerindeki etkileri araştırılmıştır. Ayrıca ele geçirilen bu depo- limerleşme ürünleri poliüretan sünger ve vernik yapımın da başlangıç maddesi olarak kullanılmış, sünger ve vernik özelliklerine etkisi incelenmiştir.

Most countries have been concerning to solve the solid waste problem whic.h is caused by increasing consumption and environmental pollution. In addition, Modern Society has been trying to reuse the solid wastes based on polymeric materials such as polyethylene (PET), polypropylene (PP), polyvinylchloride (PVC), polyethylenetrephthalate (PET). These polymeric materials are produced by condensa tion type or addition type polymerization and used in various applications induding packaging for foods and bottleing for soft drinks such as coke^ spirits, mineral water. Since both disposal of these polymeric materials after being used and transportation of waste to long distances are not economical, several methods have been developed for recycling the solid waste. These methods include chemical recycling, cracking, electrokinetic recycling, pyrolysis and incineration. Incineration method has been used for centuries to burn the waste in the open areas. But in present times, it is abondoned due to the environmental pollution considerations. Electrokinetic recycling has been used to break down plastic waste into industrial gases by use of an electric arc. Vlll Pyrolysis method is decomposition of plastic uiaste back into oil or gas using heating processes. Chemical recycling is the breakdown of polymeric waste into reusable fractions for reincarnation as polymers, monomers or chemicals. Consequently, numerous uiaste processing systems have been designed. Most of them are further developed, Mean while, addition type of polymeric waste (PE, PP.PVC) can be reused by only melting on their softening points in calendering and injection systems. Although, recycling of these plastic materials is not a serious problem and can easily be achieved, this method cannot be applied in recycling for condensation type polymeric wastes such as PET,PBT. It appears that some chemical treatments should be considered for the practical application of this method in recycling of polymeric wastes. In this study, the chemical recycling of PET scraps by glycolysis method which is a thermal treatment method that PET scraps breakdown by using various types of glycols into monomer according to the following reaction. HO+CHgC^-OİH + --O-CHgCHg-O-C-^-C-- GLYCOLS PET II O-n jr HD^CHgCHg^C^-C^CHgCHg-ojH 'TJ (I) The reaction products may in turn be repolymerized. Experiments were usually carried out in three-necked rounded bottom flask. Parameters affecting end product IX yield and composition were found to be depolymerization temperature, the type of glycol, the concentration of glycol, the type and the amount of catalyst. To test the effect of catalyst concentration, a series of depolymerization reactions were carried out. In these experiments the completion of depolymerization mas monitored at each catalyst concentration. As can be seen from the table given below, depolymerization time decreased significantly when the amount of catalyst was increased. TABLE: The effect of catalyst amount pn depolymeriza tion time. Temperature : 19D Amount of catalyst (%) Depolymerization time (minute) 3DD D.1 2i*0 0.6 120 a: in parts relative to the amount of PET and glycol mixture Moreover, further increase in catalyst concentration results in the discoloration of product and- formation of some impurities. Therefore optimal amount of catalyst was determined to be 0.6 % based on the amount of glycol and PET mixture. It is also interesting to note that reaction tem perature effects the overall depolymerization time. As shown in the table given below, the depolymerization time may conveniently be lowered by increasing the reaction temperature. TABLE: The effect of reaction temperature on the depolymerization time. PET+DEG=100 parts, Catalyst:0.6 part. Temperature (DC) Depolymerization time(minate) 200 120 220 80 230 60 However, temperatures higher than 230 C was nut employed so as tD prevent elimination reaction observed at these temperatures. In this connection, it should be pointed out that elimination reaction may be additional reason for the discoloration. Glycols with different boiling points namely, ethylene glycol, diethylene glycol, polyethylene glycols, glycerol, trimethylolpropane mere used in depolymerization experiments. In fact, these glycols are widely employed in industry for various applications. Selection of a glycol with appropriate boiling point allows us possibility to work at comparatively high temperature hence to lower the depolymerization üte Moreover, the yield Df depolymerization product may be improved by the temperature increase. Depolymerization products have two Dr three hydroxy functional end groups in their backbones. These hydroxy functional depolymerization products are expected to be aromatic in nature since starting polymer (PET) possesses aromatic group in the structure. As will be dealth later rigid aromatic group in polyol plays an important role on the properties of the product obtained in further application. Polyols were' attained by a two-step procedure. First, PET scrap was reacted with various types of glycols to yield a mixture of aromatic polyester polyol as a homogenous liquid. There was no precipitation upon standing. Subsequently, these polyols were then reacted with diisocyanates to form flexible polyurethane foam or one-component polyvrethane coating. In the former case, polyol was reacted with diiso- cyanate to gether with a blowing agent, water or both, in the presence of a catalyst such as diazo bicyclo (2.2.2) octane (DABCO). For this purpose, polyester polyol obtained from PET scraps were blended with a typical polyol (polyol *t1DD s, Dow Chemical) and reacted in the usual manner. XI K ° £3 X (D + BB X COMMERCIAL + flf1^00 > POLYURETHANE FOAM POLYOL The properties of foam were compared with commercially available polyurethane foam. Wo dimensional distortion in foam structure was observed. Foam with comparable physical properties of commercial foam mas obtained. Another application of polyols from PET scraps was one-component polyurethane coatings. This product was transesterif ied at a temperature of 23G C with urethane oils which was prepared by transesterif ication of drying oils (e.g linseed, soybean, safflower) with hydroxy functional substances such as glycerol, pentaerithritol. The resultant mixture of polyols was reacted with toluenediisocyanate. This system was air dried at ambient temperatures to give desired coating. This type of coating may practically be applied as interior ax exterior paints and varnishes. O CH2-0-C-R £0 '/. (I) + 80 '/ ÇH-OH /Cat. TDI A I f==^ Transesterified > One-Component CHE-OH "«** Product Urethane Coating Monoglyceride As an experimental demonstration, we have applied one-component urethane coating on a wood surface and mechanical properties of the coating were compared with commercially available varnish. The relevant data are given in the table below. XII TABLE: Comparision of mechanical properties between Cammerically available varnish and recycled PET modified varnishes. Hardness Dry tD touch Dry to hard (König) time (min.) time(min.) Commerically available varnish Wl 60 105 varnish produced by using 20% 35 ffl 1DD dıfunctıonal polyol of recycled PET l/arnish produced by using 20 % three 46 50 95 functional polyol of recycled PET
Chemical recycling of waste PET
Tez (Yüksek Lisans) -- İstanbul Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 1992
Keywords: Atık değerlendirme; Depolimerleşme; Plastik malzemeler; Polietilen tereftalat; Waste evaluation; Depolymerization; Plastic materials; Polyethylene terephthalate